Microstructural homogeneity and mechanical behavior of a selective laser melted Ti-35Nb alloy produced from an elemental powder mixture. (20th January 2021) - Wang, Jincheng; Liu, Yujing; Rabadia, Chirag Dhirajlal; Liang, Shun-Xing; Sercombe, Timothy Barry; Zhang, Lai-Chang
Abstract: Although using elemental powder mixtures may provide broad alloy selection at low cost for selective laser melting (SLM), there is still a concern on the resultant microstructural and chemical homogeneity of the produced parts. Hence, this work investigates the microstructure and mechanical properties of a SLM-produced Ti-35Nb composite (in wt%) using elemental powder. The microstructural characteristics including β phase, undissolved Nb particles and chemical homogeneity were detailed investigated. Nanoindentation revealed the presence of relatively soft undissolved Nb particles and weak interface bonding around Nb-rich regions in as-SLMed samples. Solid-solution treatment can not only improve chemical homogeneity but also enhance bonding through grain boundary strengthening, resulting in ∼43 % increase in tensile elongation for the heat-treated Ti-35Nb compared to the as-SLMed counterpart. The analyses of tensile fractures and shear bands further confirmed the correlation between the different phases and the ductility of Ti-35Nb. In particular, the weak bonding between undissolved Nb and the matrix in the as-SLMed sample reduces its ductility while the β grains in solid-solution treated Ti-Nb alloy can induce a relatively stable plastic flow therefore better ductility. This work sheds insight into the understanding of homogenization of microstructure and phases of SLM-produced alloys from an elemental powder mixture.